O papel dos pesticidas naturais na agricultura sustentável - Moretti, Gustavo Passarini (Universidade Federal de São Carlos, 2025)
Conventional agriculture, based on the intensive use of chemical inputs, has led to environmental impacts and health risks, such as soil and water contamination, as well as pest resistance to synthetic pesticides. Faced with these challenges, sustainable agriculture emerges as a viable alternative, promoting practices that balance productivity, natural resource conservation, and food security. In this context, biopesticides have become an essential tool in reducing dependence on synthetic agrochemicals, offering effective and environmentally friendly solutions. This study aimed to analyze the role of biopesticides in sustainable agriculture, highlighting their importance, benefits, and challenges. To achieve this, fundamental concepts were addressed, along with the problems related to chemical fertilizers, the evolution and classification of biopesticides, as well as the difficulties and opportunities associated with large-scale production and market acceptance. Additionally, widely used biopesticides, such as Trichoderma and Bacillus thuringiensis, were discussed, demonstrating their technical and economic feasibility. The findings indicate that the biopesticide market has been growing significantly, driven by stricter regulatory requirements, technological advancements, and the global demand for more sustainable agricultural practices. In Brazil, the adoption of these products is already a reality, with promising prospects for expansion in the coming years. The transition to a production model less dependent on synthetic pesticides is an irreversible path, aligned with global sustainability demands and the need for a more efficient and responsible agribusiness. It can be concluded that biopesticides are an essential alternative for the future of agriculture, contributing to food security and environmental preservation.
On the role of natural pesticides in sustainable agriculture
Keywords: Agricultura sustentável; Biopesticidas; Agroquímicos; Fertilizantes naturais; Sustentabilidade; Sustainable agriculture; Biopesticides; Agrochemicals; Natural fertilizers; Sustainability; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA